STUDIES ON PHOSPHATE SOLUBILIZATION AND PLANT GROWTH ENHANCEMENT BY RHIZOSHERIC BACTERIA - SUKHMINDERJIT KAUR,; SAMREET KAUR, (International Journal of Pharma and Bio Sciences, 2015)
A total of 28 samples were processed, of which 20 isolates were identified as phosphate solubilizing bacteria. Among 20 isolates, 12 (60 %) belonged to B. subtilis, 3 (15%) were B. brevis, 3 (15%) belonged to Pseudomonas aeruginosa and 2 (10 %) were identified as Enterobacter aerogenes. All the isolates exhibited phosphate solubilization (1.009 µg/ml to 1.609 µg/ml), produced Indole acetic acid (5.46 mg/ml 14.89 mg/ml), protease activity and ammonia production. The isolates produced hydrogen cyanide in the range of 1-5 and were able to tolerate high concentration of insecticide chemorise i.e. upto 5% (v/v). B. subtilis PSB 16 isolates gave the highest values for all plant growth promoting attributes and exhibited growth promotion in Hordeum vulgare by showing enhancement in mean root and shoot length of the plant. PSB isolates showing plant growth promoting attributes has potential to be used as biofertilizer agent.